ETNOTEKNOKONSERVASI PEMANFAATAN PALEM SEBAGAI BAHAN PEMBUATAN BUBU TRADISONAL SUKU MAYBRAT - MARIA M. BASNA; RUDI A. MATURBONGS; ANTONI UNGIRWALU (Fakultas Kehutanan UNIPA, 2020)
Traditional knowledge and local wisdom related to the utilization of natural resources of the forest developed as a multi-disciplinary in the study of ethnobiology, ethnoecology, ethnoforestry, to ethno-conservation. Unfortunately, in ethnobotany studies, there are publicity gaps in documenting ecological (biological) and cultural (social) aspects in Papua related to community-based conservation management. Therefore, it is important to conduct a study related to the documentation of community-based conservation knowledge in West Papua. The purpose of this research study is to construct ethno-noconstruction of palm plants as material for making traditional bubu by the Maybrat tribe in West Papua. The results of scoping of local knowledge of bubu making and sero making techniques of the Maybrat are part of cognitive symbols that are classified as individual life skills where the conditions are highly dependent on the state of the environment in which they live and the potential of forest resources. The use of palm trees as natural resources and the local knowledge construction process of making traditional bubu as a manifestation of the Maybrat etnotecnoconservation are closely related to people's livelihoods as active and passive fishermen. Local knowledge in the use of palm trees in the process of its formation is not merely a cognitive dimension, but also the dimension of local conservation values ​​in maintaining an environmentally friendly and sustainable fish capture system that should need to be maintained.